(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Electrochemical treatment has moved from laboratory demonstrations toward pilot and industrial deployments because it offers modular control, rapid response to influent variability, and the ability to couple separation and destruction mechanisms in compact systems. This article presents an engineering and evaluation framework for piloting electrochemical treatment under industrial conditions, with particular focus on sludge generation and management, energy and electrode consumption, and environmental-economic performance.